Encouraging Clinical Evolution of a Pediatric Patient With Relapsed Diffuse Midline Glioma Who Underwent WT1-Targeting Immunotherapy: A Case Report and Literature Review - Hashii, Yoshiko; Oka, Yoshihiro; Kagawa, Naoki; Hashimoto, Naoya; Saitou, Hiroyuki; Fukuya, Syogo; Kanegae, Mizuki; Ikejima, Sayaka; Oji, Yusuke; Ozono, Keiichi; Tsuboi, Akihiro; Sugiyama, Haruo (Frontiers in Oncology, 2020)
Diffuse midline glioma (DMG) in children is a highly aggressive, malignant brain tumor that is fatal when relapsed. Wilms tumor 1 (WT1) is a high-priority antigen target for cancer immunotherapy. We hereby report on a pediatric patient who had DMG that regrew after chemoradiotherapy and underwent WT1 peptide vaccination. A 13-year-old Japanese boy presented with vertigo, diplopia, and right hemiplegia at the initial visit to another hospital, where he was diagnosed with DMG by magnetic resonance imaging (MRI); DMG was categorized to histological grade IV glioma. The patient underwent radiotherapy and chemotherapy with temozolomide. After three cycles of chemotherapy, MRI revealed tumor regrowth that translated into deteriorated clinical manifestations. Immunohistochemically, the H3.3K27M mutation in the biopsy specimen was confirmed and the specimen was positive for WT1 protein. The patient underwent WT1-targeting immunotherapy with the WT1-specific peptide vaccine because of having HLA-A*24:02. Consequently, his quality of life drastically improved so much as to the extent that the patient became capable of conducting nearly normal daily activities at weeks 8 to 12 of vaccination. MRI at week 8 of vaccination revealed an obvious reduction in the signal intensity of the tumor. Furthermore, betamethasone dose could be reduced successively (4, 1, and 0.5 mg/day at weeks 4, 5, and 7, respectively) without deteriorating clinical manifestations. Best response among responses assessed according to the Response Assessment in Neuro-Oncology criteria was stable disease. Overall survival was 6.5 months after vaccination onset and was 8.3 months after relapse; the latter was markedly longer than the reported median OS of 3.2 months for pediatric patients with relapsed DMG in the literature. Modified WT1 tetramer staining revealed the WT1 peptide vaccine-induced production of WT1-specific cytotoxic T cells, and the interferon-γ (IFN-γ) ELISpot assay of peripheral blood mononuclear cells disclosed the production of IFN-γ. Delayed-type hypersensitivity test became positive. Any treatment-emergent adverse events did not occur except injection site erythema. Our pediatric patient exhibited an encouraging clinical evolution as manifested by stable disease, improved clinical manifestations, steroid dose reductions, a WT1-specific immune response, and a good safety profile. Therefore, WT1-targeting immunotherapy warrants further investigation in pediatric patients with relapsed DMG.